A cool response—The influence of ambient temperature on capillary refill time. Issue 6 (5th March 2018) - John, Rani Toll; Henricson, Joakim; Junker, Johan; Jonson, Carl‐Oscar; Nilsson, Gert E.; Wilhelms, Daniel; Anderson, Chris D.
Abstract : Objective: To describe the effect of low ambient temperature on skin temperature and capillary refill (CR) time in forehead, sternum and finger pulp. Methods: An observational, nonrandomized experimental study on 15 healthy subjects (6 females) in a cold room (8°C). Outcome measures were skin temperature and quantified CR test after application of a standardized blanching pressure (9 N/cm 2 ) using digital photographic polarization spectroscopy to generate CR times. Results: The finger pulp showed marked temperature fall and prolonged CR times (>10 seconds). The CR registrations of the forehead and sternum were more comparable to curves observed in a control material at room temperature, and skin temperature falls were less marked. CR times were not prolonged in forehead measurements. At the sternum, some individuals showed CR times beyond guideline recommendations despite only a marginal reduction in skin temperature. Conclusions: Low ambient temperature is a strong independent factor for CR time at peripheral sites. Reservation about sternum as a site of measurement is warranted since cold provocation produced prolonged CR times in some individuals. We found that the forehead is the most thermostable of the 3 sites and thus the preferred site to avoid ambient temperature artifact in measuring CR time. Abstract : Polarized reflectance spectroscopy enables quantitative assessment of the capillary refill (qCR) test. Low‐ambient temperature is a strong independent factor for CR time at peripheral sites. qCR test was performed in a cool room (8°C) at 3 sites; forehead, sternum and finger. The forehead was the most thermostable of the 3 sites and thus the preferred site to avoid ambient temperature artifact in measuring CR time.